2019
DOI: 10.1017/s1049096519001124
|View full text |Cite
|
Sign up to set email alerts
|

Let’s Talk about Sex: Examining the Factors Influencing Congressional Response to #MeToo on Twitter

Abstract: This article examines the factors that influence whether members of Congress tweet about the #MeToo movement. Whereas social-identity theory suggests that congresswomen would be more likely to tweet about #MeToo, congressional research argues that increased polarization has resulted in congresswomen bucking gender stereotypes and embracing more partisan behavior than might otherwise be expected (Pearson and Dancey 2011). We examine how gender, partisanship, and ideology shape the Twitter activity of members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…This, in turn, should lead female legislators to prioritize these kinds of issues compared with their male counterparts. Research on sexual harassment, for instance, has shown that gender has a significant impact on not only whether people believe sexual harassment has happened, but what the outcomes of such cases should be (Clark and Evans 2020;DeSouza and Solberg 2004;Ford and Donnis 1996;Konrad and Gutek 1986;Weber, Bauer, and Martinez 2012). Women are more likely to seek harsher punishments for those who have been accused of committing sexual harassment and assault, especially if those women work in more male-dominated fields (Weber, Bauer, and Martinez 2012).…”
Section: Who Should Support #Metoo?mentioning
confidence: 99%
See 3 more Smart Citations
“…This, in turn, should lead female legislators to prioritize these kinds of issues compared with their male counterparts. Research on sexual harassment, for instance, has shown that gender has a significant impact on not only whether people believe sexual harassment has happened, but what the outcomes of such cases should be (Clark and Evans 2020;DeSouza and Solberg 2004;Ford and Donnis 1996;Konrad and Gutek 1986;Weber, Bauer, and Martinez 2012). Women are more likely to seek harsher punishments for those who have been accused of committing sexual harassment and assault, especially if those women work in more male-dominated fields (Weber, Bauer, and Martinez 2012).…”
Section: Who Should Support #Metoo?mentioning
confidence: 99%
“…Other scholarship demonstrates that women in Congress espouse a women's issue agenda, prioritizing issues that disproportionately affect women through their bill sponsorship and cosponsorship, floor speeches, and voting behavior (Pearson and Dancey 2011;Swers 2002;Thomas 1991). Clark and Evans (2020) show that when it came to the early stages of the #MeToo movement, gender mattered a great deal as to whether members of Congress tweeted about the movement. Partisanship had very little to do with it, as members of both parties sent tweets in support of the movement.…”
Section: Who Should Support #Metoo?mentioning
confidence: 99%
See 2 more Smart Citations
“…It is much easier, given their legal expertise, for Democrats and Republicans who earned juris doctorates and may have even practiced law, to weigh in on the constitutionality of President Trump's actions. 12 Finally, there are some other factors likely to play a role in conditioning congresspersons' tweeting on the scandal: such as gender, since past studies often find an imbalance in tweeting on the basis of sex (Clark & Evans, 2020;Evans, 2016;Evans & Clark, 2016). Relatedly, President Trump has contributed to one of the historically largest gender gaps in presidential voting and hence it is likely that female Democratic members were one of the most vociferous groups taking to Twitter to denounce Trump's conduct (Wagner et al, 2017).…”
Section: Twitter and The Ukraine Whistleblower Scandalmentioning
confidence: 99%